When it is more than flu: case report of a viral myositis - Maciel, Miguel (2022)
Background: Upper respiratory tract infections are one of the most common motives for acute consultation in primary health care in children. Regardless, less common diseases, such as myositis, should be considered. Content: Our eight-year-old male was observed at our primary health care unit in November 2019 with a two-day evolving fever and cough with no findings in the physical examination – a viral upper respiratory tract infection was assumed and treatment with antipyretic drugs and oral hydration was indicated. Three days later he returned with the maintenance of his clinical status, regardless of treatment, with abnormal gait and bilateral pain in the gastrocnemius muscle. The neurological and osteoarticular physical examination had no abnormalities. Nevertheless, he was referred to the pediatric emergency department for further evaluation. The emergency department had no additional findings in the physical examination. Blood tests were performed, which revealed a creatine kinase of 7110U/L, myoglobin of 1935ng/mL, and aspartate aminotransferase of 191U/L, with no changes in renal function. He was then admitted for intravenous fluid therapy with suspected myositis. The nasopharyngeal aspirate culture was performed and tested positive for Influenza B virus – Influenza B myositis was the presumed diagnosis. Treatment with oseltamivir was done for four days with a good response. He was discharged after four days with an indication to increase oral hydration and rest. Conclusion: One should look for rarer symptoms in flu-like presentations and increase accessibility for patient re-evaluation.